Development of Google Sites-Based Interactive Multimedia for Sixth-Grade Solar System Instruction - Akhmad Taufiq; Suryanti Suryanti; Enny Susiyawati; Neni Mariana (Papanda Publisher, 2026)
This study aims to develop and evaluate Interactive Multimedia (IMM) learning media based on Google Sites and supported by Google Classroom to improve learning motivation and learning outcomes of sixth-grade students at SDN Bening, Mojokerto, on Solar System material. The study used a Research and Development approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Research subjects involved 3 experts (media, material, and instructional), 1 science teacher, and 22 students. Data collection instruments included validation sheets, response questionnaires, and learning outcome tests (pretest–posttest). Data were analyzed descriptively using percentages and N-Gain scores. The results showed that the developed IMM media was highly valid according to expert judgment (average score of 4.28), highly practical based on teacher (4.40) and student (4.34) responses, and effective in improving student learning outcomes, as indicated by an N-Gain score of 0.54 (moderate category). Student learning motivation increased by 21.32% after implementation. The integration of Google Sites and Google Classroom supports interactive content delivery and digital assessment within a unified learning environment, making the media suitable for teaching abstract science concepts at the elementary level.